Reasons of drug use among adolescents: implications for clinical nursing care - Francisco Rafael Ribeiro Soares; Deceles Ingrid de Carvalho Oliveira; Joana Darc Martins Torres; Vera Lúcia Mendes de Paula Pessoa; José Maria Ximenes Guimarães; Ana Ruth Macêdo Monteiro (SciELO, 2020)
Abstract This is a theoretical essay which aims to reflect on the reasons for and why adolescents use drugs and their implications for clinical nursing care. It used the referential of social phenomenology of Alfred Schutz. The main reasons identified were: to attenuate existential crisis, form social bonds and to have fun. The reasons for this are related to the characteristics of adolescence, a breakdown in social and family ties and the conditions of programmatic vulnerability. Motivations provide important information for developing person-centered, not drug-abuse-centered care strategies. Nurses' caregiving action is based on emancipatory health education strategies grounded on the strategy of reducing harm and risks related to drug use and the possibility to help adolescents become aware of their biographical situation in a face-to-face relationship, so that they can (in knowing yourself) act to promote their health.